A Comparative Study of Social Education in the Primary Education of Iran and Japan - Maliheh Rabiei; Irandokht Fayyaz; Tayebeh Mahrouzade; Abolfazl Bakhtiari; Ali Khorsandi Taskooh (Comparative Education Society of Iran ( CESIR), 2019)
The purpose of the present paper is to compare social education in the educational system of Iran and Japan from the perspective of macro policies and content analysis of primary school textbooks. The research method is comparative (qualitative type)usingBereday's Analysis Approach to analyze data. The unit of analysis and level of observation is "macro" (country) sampling strategy is "different social systems, different educational outcomes" based on the "making stranger familiar" approach.To collect data, educational resources such as national documents, Ministry of Education reports, elementary school textbooks, and journal articles and books were used.The findings of the study showed that main Iran's educational policies on social education influenced by the three factors of national identity, Islamic identity and modern identity, while in Japan macro education policies are influenced by Buddhist and Shinto religion, Confucianism, nationalism and modernism.The Japanese education system in primary education compared to the Iranian education system has a much stronger policy and process focus on the social education of children. According to this study, the upstream documents of the Japanese education system strongly emphasize the increasing role of modernism (as opposed to other factors) and the teaching of concepts such as the environment, global issues, international understanding, cultural exchanges, citizenship, the future of the world and the role of Japan.In addition, the findings show that the time allocated, and the variety of topics related to social education in Japanese primary education is more than that of Iran.The key recommendation of this study is to reconsider and recreate strategic approaches to social education and to focus on formal (intentional) and informal (hidden) education programs on the real and daily social life of children in Iranian primary education.